TINJAUAN HUKUM PERLINDUNGAN DATA PRIBADI DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Safitri, Anissa (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACTPersonal data protection is a form of protection for a right to privacy, it will require protection of a person's privacy or protection of a person's personal data. To find out the protection of personal data is regulated in the Laws and Regulations in Indonesia and to find out the obstacles to the protection of personal data in law and their solutions.Normative legal research method (normative legal research) research specifications in analytical descriptive, the data used are primary data, secondary data and tertiary data, data collection tools with literature studies with qualitative analysis approach techniques.The results of the Personal Data Protection study in Indonesia are regulated in Law Number 27 of 2022 concerning Personal Data Protection, Law No. 11 of 2018 concerning Information and Electronic Transactions, amendments to Law No. 19 of 2016 concerning Regulation of the Minister of Communication and Informatics of the Republic of Indonesia Number 20 of 2016 concerning Protection of Personal Data in Electronic Systems, and has obstacles in the application of the Law such as overlapping old and new laws, it is mandatory to form a Personal Data Protection Institution which is very much needed and important considering the existence of a strong legal basis, namely in Article 58 of the Personal Data Protection Law and seeing the conditions of personal data violation cases in Indonesia which are increasing every year. The institution plays a role and is tasked with supervising, protecting, and enforcing individual privacy rights and supervising the use of personal data by personal data controllers. KEYWORDS: Personal Data Protection